Screening anti-cancer compounds from palm oil industrial wastes - Ahmad Raus, Raha; Shamsudin, Syamsa Shazwan; Jamal, Parveen (IIUM Press, 2011)
In this srudy. ami-nlmor promoting activity against breast cancer cells (MCF7) of palm oil industrial waSIl'S crudc cxtracl was inwstigated. Methanol and waleI' extracts of lhe industrial wasIl'S ,,'crc lestI'd using MTT assay. Thc mosl active exlracl for inhibition of lhe prolifcrdlion of breast cancer cell was mcthanolic extract of palm leaf waSIl'. All of the other industrial waSle extracts also showed anli-eancer aClivily excepl for aqueous extl'llcf of palm oil mill effluenl (POME), wilh respect to thesc results. palm leaf wastes coutd he studied funher for their potential 10 treat breast canccr ceUs.